Соціологія племені (на прикладі племінної організації Беніну) - Гусаков, В. (Народна творчість та етнографія, 2007)
Article is devoted to the discovering sociology of a tribe as a modern social phenomenon. Benin is taken as an example, which has highly developed and rather typical African tribal system. Article will be useful for all who are interested in problems of human society genesis.